An interesting case of seronegative neuro myelitis optica spectrum disorder - Sriharsha, Tirumalasetty; Kumar M., Sathish; Kumar, A. Arun; Raj J., Raghav; V., Vikrannth; Raghavan, Vinod; Rajendran, Kannan (International Journal of Advances in Medicine, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune disease that causes severe demyelination, especially in the optic nerve and spinal cord with typical clinical manifestations of acute optic neuritis and transverse myelitis. Seventy to ninety percent of the cases of NMOSD test positive for aquaporin 4 IgG Antibodies (AQP4 IgG Ab). Here we report a case of 22-year-old female who presented with history of diffuse headache since 1 week, history of double vision since1 week and excessive day time sleepiness since2 months. Patient had a past history of bilateral and simultaneous optic neuritis 9 months back. On further evaluation patient was diagnosed as seronegative NMOSD (AQP4 IgG Ab–negative).